Diskurzivna narava stereotipov in predsodkov ter soočanje z njimi v sodobni demokratični družbi - Mikolič, Vesna (Jezik in slovstvo, 2008)
Following from the idea of tolerance and dialogue as fundamental concepts of contemporary democratic society, the paper defines the role of stereotypes andprejudices in these democratic ideals. On the one hand, the discursive nature of prejudices enables them to become obstinate ideological constructs, while, on the other hand, it also indicates their mutability. In any case, we witness contemporary changes in prejudices, which are becoming ever more covert, and observe their tendency to appear in certain new areas. With such fundamental changes in the development of prejudicial thinking it is even more important to develop ways to efficiently confront these changes. In the last part of the paper the results of research amongst the secondary school population in the city of Koper are presented. These results confirm the efficiency of so-called contact strategies in increasing awareness of stereotypes and prejudices.
Keywords: demokratična družba; diskurzivne študije; predsodki; social psychology; socialna psihologija; sociolinguistics; sociolingvistika; stereotipi